Solid Waste Management in Sidoarjo at Present: Pengelolaan Sampah di Sidoarjo Saat Ini - Rosnawati , Emy; Multazam , Mochammad Tanzil; Maryati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2022)
Environmental pollution causes an increase in the spread of disease, reduction of environmental aesthetics and an impact on global warming. On the other hand, well-managed waste will improve public health as well as the quality of the environment and will turn the waste into a resource. The waste problem has become a serious problem, one of which is in Sidoarjo. Due to the current density of the population, the Sidoarjo government is overwhelmed in handling the increasing volume of waste that comes from the results of people daily activities. Waste management in Sidoarjo is regulated in Regional Regulation number 6 of 2012 about waste management. The purpose of the study was to determine the current management of solid waste in Sidoarjo. The method used is sociological juridical with an empirical approach. The data collection in this study used interview, observation and documentation techniques. The data analysis used was induction. The results of this study indicate that waste management in Sidoarjo is already in accordance with the existing regulations, namely Regional Regulation of Sidoarjo number 6 of 2012 concerning waste management. However, there is something that must be improved, which is the lack of public awareness in waste management.